New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean - Angulo, Arturo; López-Sánchez, Myrna I. (Zootaxa, 2017)
New records of occurrence for four species of lampriform fishes (Teleostei: Lampriformes; Desmodema polystictum, Regalecus russelii, Trachipterus fukuzakii and Zu cristatus) poorly known or previously unknown for the Pacific coast of lower Central America (Costa Rica-Panama) are herein reported. Museum specimens supporting such records are characterized and described. Comparative morphometric and meristic data on other collections and species of lampriforms, as well as distributional information, are provided and discussed. Diversity, taxonomy and distribution of the eastern Pacific species of the order also are briefly discussed. Finally, a key to the eastern Pacific species of the Lampriformes, based on our research and data available in the literature, is presented.